2021
DOI: 10.1186/s13098-021-00623-w
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery can acutely modulate ER-stress and inflammation on subcutaneous adipose tissue in non-diabetic patients with obesity

Abstract: Background Bariatric surgery, especially Roux-en-Y gastric bypass (RYGB), is the most effective and durable treatment option for severe obesity. The mechanisms involving adipose tissue may be important to explain the effects of surgery. Methods We aimed to identify the genetic signatures of adipose tissue in patients undergoing RYGB. We evaluated 13 obese, non-diabetic patients (mean age 37 years, 100% women, Body mass index (BMI) 42.2 kg/m2) one d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…Moreover, Gregor et al [ 18 ] reported reduced expression of ER stress markers in the liver (glucose-regulated protein 78 kDa (GRP78), phosphorylated eukaryotic translation initiation factor 2A (p-EIF2α)), subcutaneous adipose tissue (X-box binding protein 1 (sXBP1), GRP78, CHOP and p-EIF2α) one year after RYGB intervention. In line with this, Ferraz Bannitz et al [ 19 ] observed a drop in ER stress expression (PERK and calreticulin(CALR)) in subcutaneous adipose tissue 3–6 months after surgery. Both studies described changes mainly in transcripts in subcutaneous adipose tissue; as far as we are aware, we are the first group to describe the effects of RYGB on ER stress protein markers in leukocytes.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Moreover, Gregor et al [ 18 ] reported reduced expression of ER stress markers in the liver (glucose-regulated protein 78 kDa (GRP78), phosphorylated eukaryotic translation initiation factor 2A (p-EIF2α)), subcutaneous adipose tissue (X-box binding protein 1 (sXBP1), GRP78, CHOP and p-EIF2α) one year after RYGB intervention. In line with this, Ferraz Bannitz et al [ 19 ] observed a drop in ER stress expression (PERK and calreticulin(CALR)) in subcutaneous adipose tissue 3–6 months after surgery. Both studies described changes mainly in transcripts in subcutaneous adipose tissue; as far as we are aware, we are the first group to describe the effects of RYGB on ER stress protein markers in leukocytes.…”
Section: Discussionmentioning
confidence: 64%
“…However, only a few studies have evaluated the effect of bariatric surgery on AMPK in humans. Increased expression and activity of AMPK was reported in subcutaneous adipose tissue 3–6 months after RYGB, and was accompanied by a reduction in oxidative stress, ER stress and inflammatory markers [ 19 , 38 ]. Similarly, AMPK activity was found to be increased in PBMCs one year after bariatric surgery—via laparoscopic bypass or sleeve gastrectomy—inducing chaperone-mediated autophagy, a reduction in protein oxidative damage and hsCRP [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an ovariectomized menopausal mouse model shows that Nrf2 KO gain more bodyweight than control mice [ 117 ]. In humans, it is noteworthy that obese patients undergoing Roux-en-Y gastric bypass show elevated expression of Nrf2 in adipose tissue after surgery [ 118 ]. Taken together, these results suggest that Nrf2 in adipose tissue has a beneficial effect on obesity-related insulin resistance.…”
Section: Role Of Nrf2 Agonism In Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…In 2017, a study conducted on 47 men with morbid obesity reported a significant decrease in the salivary oxidative markers (levels of lipid peroxidation, oxidation protein products, and 8-hydroxy-D-guanosine) six months after bariatric surgery [ 149 ]. Three months after gastric bypass, the gene expression profiles of obese nondiabetic patients were also reportedly altered, with an increased expression in the genes (SOD2, Sirtuin 1, Sirtuin 3, and Nuclear factor erythroid 2-related factor 2) involved in the cellular response to oxidative stress [ 150 ]. Weight loss in bariatric surgery improves the total antioxidant capacity, which correlates with an improvement in the BMI, waist-to-hip circumference, serum insulin, and uric acid [ 147 ].…”
Section: Management Of Male Hypogonadism Associated With Non-communicable Chronic Diseasesmentioning
confidence: 99%